2023
DOI: 10.1021/acs.jafc.2c08277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Molecular Weight Glutenin Subunits (HMW-GSs) on Gluten Polymerization during Biscuit Making: Insights from Experimental and Molecular Dynamics Simulation Study

Abstract: The effect of high-molecular weight glutenin subunits (HMW-GSs) on gluten polymerization during biscuit making was investigated using a set of HMW-GS deletion lines. Results showed that the deletion of HMW-GSs improved the biscuit quality compared with the wild type (WT), especially in x-type HMW-GS deletion lines. Slight gluten depolymerization was observed during dough mixing, while progressive gluten polymerization occurred during biscuit baking. The deletion of HMW-GSs suppressed the polymerization of glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Each locus has two closely linked genes controlling the x-and y-type subunits, and variation generated by different combinations of these loci affect wheat flour products and processing quality . At present, the influence of HMW-GS on the processing quality of bread, noodles, and biscuits is relatively well understood (Carrillo et al 1990;Li et al 2016;Yang et al 2023), and the baking quality of biscuits and bread with subunits 17+18 and 5+10 are higher (Brönneke et al 2000;Sharma et al 2002), which appears more frequently in European hexaploid wheat. Zhu et al (2001) showed that the total rating of steamed bread was greater for the subunit 5+10 versus 2+12, but Fan et al (2005) recorded that the subunit 5+10 had the undesirable effect of increasing product stickiness.…”
Section: Introductionmentioning
confidence: 99%
“…Each locus has two closely linked genes controlling the x-and y-type subunits, and variation generated by different combinations of these loci affect wheat flour products and processing quality . At present, the influence of HMW-GS on the processing quality of bread, noodles, and biscuits is relatively well understood (Carrillo et al 1990;Li et al 2016;Yang et al 2023), and the baking quality of biscuits and bread with subunits 17+18 and 5+10 are higher (Brönneke et al 2000;Sharma et al 2002), which appears more frequently in European hexaploid wheat. Zhu et al (2001) showed that the total rating of steamed bread was greater for the subunit 5+10 versus 2+12, but Fan et al (2005) recorded that the subunit 5+10 had the undesirable effect of increasing product stickiness.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review has explored the potential applications of wheat gluten nanofibers, fabricated via electrospinning, in areas such as drug release, biological scaffolds, and active food packaging . Gluten, the predominant storage in wheat flour, comprises two main types based on their solubility in aqueous ethanol: insoluble glutenin and soluble gliadin . The high-molecular-weight glutenin subunits form a structural framework through intermolecular disulfide bonds, while the low-molecular-weight glutenin subunits associate with this framework via disulfide bonds…”
Section: Introductionmentioning
confidence: 99%